Peran World Trade Organization (WTO) dalam Menyelesaikan Sengketa Dagang Antara Uni Eropa dan Indonesia Terkait Kebijakan Pelarangan Ekspor Mineral Mentah Nikel - Ridho Kamal, Mohammad Fedra; Fadhilus Sabiq, Muhammad; Ramonieta, Nadia (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
The background of this research is the WTO as an international trade organisation under the economic and social council is authorised to regulate international trade as well as resolve international trade disputes. As for nickel as a potential raw mineral material in terms of economic value and a source of world electricity, it then became an issue when Indonesia issued a policy to ban the export of nickel raw minerals. The purpose of this research is to find out the implications of Indonesia's nickel export ban on international trade, and to find out the WTO dispute settlement system in the nickel case between Indonesia and the European Union. This type of research uses descriptive analysis research that describes the results of the author's analysis. The result of this research is that there are 2 (two) types of implications of Indonesia's defeat of the European Union's lawsuit related to the ban on exports of nickel raw materials, namely legal implications which can be in the form of imposing an obligation to pay losses to the plaintiff and non-legal implications, namely disrupting the downstream of nickel mining in Indonesia.